P-85 IMPACT OF TECHNICAL NOTE No 32/2021 ON THE RATE OF LIVER TRANSPLANTS FOR REFRACTORY ASCITIS IN A TERTIARY HOSPITAL - Guilherme Massote Fontanini; Juarez Roberto de Oliveira Vasconcelos; Marcia Guimarães Villanova; Fernanda Fernandes Souza; Roberta Chaves Araújo; Rebbeca Dias Zaia; Mariana Carvalho Caleffi; Gustavo Pereira Peixoto; Isabela Dourado de Carvalho (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Liver transplantation (LT) is the definitive treatment for decompensated cirrhosis and liver failure. Patients with ascites refractory to the use of diuretics fit the criteria for a special situation, according to technical note No. 32/2021, issued in 2021 by the Ministry of Health (MS). Cases with refractory ascites now directly and immediately receive 29 points on the MELD score. Thus, changes in the waiting time for LT are expected after the aforementioned technical standard, but the real impact on morbidity and mortality is unknown.This study aims to compare the waiting time for LT for refractory ascites before and after technical note No. 32/2021. In addition, the study will also evaluate the proportion of those transplanted for refractory ascites after the 2021 resolution. Patients / Materials and Methods: The electronic medical records of patients undergoing LT in a tertiary service during the years before (2018 and 2019) and after (2022 and 2023) technical note No. 32/2021 were evaluated. Patients undergoing LT of both sexes and aged 18 or over were included. The data was stored in a spreadsheet and compared. Results and Discussion: There was a 59-day reduction in the median waiting time, considering the interval between the special situation being granted and the actual LT being performed. In addition, there was a 5.85% increase in the number of LT for refractory ascites, considering the years 2018 and 2019 versus 2022 and 2023. Conclusions: The implementation of technical note No. 32/2021 correlated with a reduction in the waiting time for LT for patients with refractory ascites. In addition, the implementation of this resolution was also correlated with a small increase in the number of transplants for refractory ascites. Despite the initial results, a longer observation period is needed for more in-depth analyses of survival and morbidity.